The Process and Significance of Convening a Community Advisory Board With Individuals With Severe Mental Illness - Jacelyn Biondo; Nia Johnson (Journal of Participatory Research Methods, 2025)
Individuals with lived experience of being diagnosed with severe mental illness and/or substance use disorders have deep and profound knowledge regarding the culture and needs of their community. Historically, these and other vulnerable populations have been excluded from care access, treatment insights, research development and participation, and often society in general. In this paper, we share our experience of convening a community advisory board with vulnerable populations and highlight the expertise these community members provide. We outline our processes of convening the community advisory board, engaging in collaborative meetings, revising the research protocol, and exploring future research needs. Using meeting minutes, conversations, and reflections we share our trauma-informed process of developing relationships with community members, with particular attention to the specific needs and significant value of working with vulnerable populations. Our intention is to outline our processes in the collaborative relationship through which we improved our research protocol due to community advisory board members' thoughtful contributions. Individuals with severe mental illness offer perspectives from a lived experience that is invaluable in the development of significant, useful, trauma-informed, and timely research for vulnerable communities. Based on our findings and experiences, we recommend that researchers convene and collaborate with community members at each stage of the research processes from inception to completion.